Exploring the driving factors of international performance: evidence from business service SMEs in Malaysia - Ahmad, Norwan; Ng, Siew Imm; Kamal Basha, Norazlyn; Abdul Aziz, Yuhanis (Centre of Sociological Research, 2023)
This study sought to improve understanding of the factors that drive the international performance (IP) of business service small andmedium-sized enterprises (SMEs), particularly from a developing country’s perspective. Studying the SME context is key in light ofthe scarce evidence of SMEs’ experience in the literature despite their increasing importance in the provision of services to international clients. Semi-structured interviews underpinned by resourcebased theory and dynamic capability view, were conducted with 11 informants representing government agencies, trade associations, and industry members. This qualitative method was employed to analyse the viewpoints of multiple industry stakeholders to enable us to capture the factors that drive IP. The findings revealed a convergence of views among the stakeholders on specific internal and external factors they perceive as essential in driving IP. The internal factors include human capital, entrepreneurial orientation, foreign market knowledge, relational capital, marketing capability, technological capability, and innovative service offerings, whereas the external factors encompass track record, access to financing, and government facilitation. We elaborated on the identified factors in relation to the supporting theories, thereby enhancing existing knowledge on their relationship with IP.